Life history, population dynamics and conservation status of Oldenburgia grandis (Asteraceae), an endemic of the Eastern Cape of South Africa - Swart, Carin (Rhodes University, Faculty of Science, Botany Department, 2008)
Oldenburgia grandis is a rare, long-lived woody paleoendemic of the Fynbos Biome of South Africa. Confined to quartzite outcrops, it has a small geographic range and narrow habitat specificity. O. grandis responds to its fire-prone environment by resprouting. Elasticity analysis of O. grandis reveals that growth and fecundity were traded off for persistence of adult, mature and sapling stages. Morphological adaptations such as a corky fire-resistant bark and the ability to resprout after fire are traits that O. grandis have evolved to persist in a frequently disturbed environment. Population growth rate for sites undisturbed by fire for a number of years (l = 1.01) and sites at various stages of recovery after fire (l = 1.00) were very similar. The highest variation in transition probabilities for all sites was seen in the persistence of the seedling stage and growth from seedling to sapling. Observed population structure and stable stage distribution determined by the matrix model show that sites recently undisturbed by fire had high abundances of the adult and sapling stages. A peak in sapling stages was seen for the stable stage distribution where similar peak in sapling numbers were seen for population structures of sites at various stages of recoveryafter fire. Favourable environmental conditions for the persistence of O. grandis populations include no fire with transition probabilities between the observed minimum and maximum and fire frequency at a 10 year interval where seedling protection from the fire is high and adult and mature mortalities during the fire are low. Stochastic environmental events that could put populations (particularly small populations) at an increased risk of extinction include high to moderate fire intensities where seedling protection from the fire is low and adult and mature mortalities are high as a result of the fire.
Keywords: Compositae; Fynbos ecology -- South Africa -- Eastern Cape; Endemic plants -- South Africa -- Eastern Cape; Rare plants -- South Africa -- Eastern Cape; Plant populations -- South Africa -- Eastern Cape; Vegetation dynamics -- South Africa -- Eastern Cape; Plant conservation -- South Africa -- Eastern Cape; Endangered species -- South Africa -- Eastern Cape